2017
DOI: 10.1093/hmg/ddw389
|View full text |Cite
|
Sign up to set email alerts
|

Decreased WNT/β-catenin signalling contributes to the pathogenesis of dilated cardiomyopathy caused by mutations in the lamin a/C gene

Abstract: Cardiomyopathy caused by lamin A/C gene (LMNA) mutations (hereafter referred as LMNA cardiomyopathy) is characterized by cardiac conduction abnormalities and left ventricular systolic dysfunction predisposing to heart failure. Previous cardiac transcriptional profiling of LmnaH222P/H222P mouse, a small animal model of LMNA cardiomyopathy, suggested decreased WNT/β-catenin signalling. We confirmed decreased WNT/β-catenin signalling in the hearts of these mice by demonstrating decreased β-catenin and WNT protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 49 publications
1
75
0
1
Order By: Relevance
“…Several groups have documented downregulation and/or abnormal localization and/or activity of connexins (known as gap junction remodeling) in experimental and human cardiomyopathies, including those induced by mutations in LMNA [9][10][11], which seems to predispose to cardiac conduction alterations. The expression of CX43 is modulated by diverse intracellular signaling pathways that can be impaired by the presence of LMNA mutation [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have documented downregulation and/or abnormal localization and/or activity of connexins (known as gap junction remodeling) in experimental and human cardiomyopathies, including those induced by mutations in LMNA [9][10][11], which seems to predispose to cardiac conduction alterations. The expression of CX43 is modulated by diverse intracellular signaling pathways that can be impaired by the presence of LMNA mutation [11].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CX43 is modulated by diverse intracellular signaling pathways that can be impaired by the presence of LMNA mutation [11]. Recently, Le Dour and collaborators showed that hearts of Lmna H222P/H222P mice have reduced WNT and β-catenin expression levels, being this latter less able to interact, on one hand, with the gene encoding CX43 to maintain its transcription and, on the other hand, with CX43 as part of a complex with the intercalated disc [9]. Here, we found that CX43 expression level and conduction defects were improved by drug-induced activation of the WNT/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The first and better described pathway starts from activation of Erk 1/2 signaling leading to a profibrotic process, which encompasses TGFbeta 2-dependent activation of connective tissue growth factor [7,8]. The pathogenicity of Erk 1/2 activation has been proven in preclinical models.…”
Section: Pathogenetic Pathways In Cardiolaminopathiesmentioning
confidence: 99%
“…Mechanosignalling is particularly relevant in conduction tissue, which deserves better investigation. In this respect, it is worth mentioning that reduced connexin 43 amount at the intercalated disks and altered disk morphology are linked to defects in Wnt/betaCatenin signaling in laminopathic heart [8]. …”
Section: Pathogenetic Pathways In Cardiolaminopathiesmentioning
confidence: 99%
See 1 more Smart Citation